IMPROVING WATER QUALITY AND PRODUCTIVITY OF TILAPIA (Oreochromis niloticus) USING CONSTRUCTED WETLAND - Eri Setiadi; Lies Setijaningsih (Indonesian Aquaculture Journal, 2011)
Organic and inorganic pollutants such as N, P, and heavy metals are a serious problem in water bodies (lake, reservoir, river, and stream) and have deleterious effects to pond productivity and human health. These pollutants produced from anthropogenic activities (i.e. industrial, agricultural, and settlement) are released into the water bodies and causing poor water quality. Constructed wetland (CW) is one of the technologies that have the capability to solve such problems. The purpose of this experiment was to examine the efficiency of constructed wetland in terms of reducing pollutants from the stream as a water resource for aquaculture area and increasing fish production. Two kinds of treatments were set up: one fish pond culture with constructed wetland and the other one without constructed wetland (control). Each treatment consisted of three replications. The result showed that water quality in the fish pond with CW was better than the control. Constructed wetland were able to reduce ammonia (NH3-N), nitrite (NO2-N), nitrate (NO3-N), TN, phosphate (PO4-P), TP, Cu, Pb, and As concentrations to 15.00%-88.27%, 9.52%-72.73%, 11.11%-57.14%, 20%-66.67%, 24.44%-80.77%, 12.04%-77.95%, 50.00%-100%, 56.25%-100%, and 46.83%-100%, respectively. Nile tilapia cultured in pond using CW was higher than the control in terms of total length, body weight, and survival rate. The t test revealed that nile tilapia (Oreochromis niloticus) cultured in pond with CW and the control has significant difference (P<0.01) in terms of total length, body weight, and survival rate. This is the evidence that constructed wetland technology is very useful on improving water quality and increasing pond productivity of nile tilapia cultured in the freshwaterpond.